2021
DOI: 10.1002/ange.202104863
|View full text |Cite
|
Sign up to set email alerts
|

Bioorthogonal Hydroamination of Push–Pull‐Activated Linear Alkynes

Abstract: A bioorthogonal reaction between N,N-dialkylhydroxylamines and push-pull-activated halogenated alkynes is described. We explore the use of rehybridization effects in activating alkynes, and we show that electronic effects, when competing stereoelectronic and inductive factors are properly balanced, sufficiently activate a linear alkyne in the uncatalyzed conjugative retro-Cope elimination reaction while adequately protecting it against cellular nucleophiles. This design preserves the low steric profile of an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…More recently, other bioorthogonal reactions have been developed, including strain‐promoted alkyne‐nitrone cycloadditions (SPANC), [11] isonitrile‐based [4+1] cycloadditions, [12] and cycloaddition reactions between o‐quinones and strained alkenes and alkynes [13] . Very recently, Kim and co‐authors introduced a new class of bioorthogonal reactions, i. e., the retro‐Cope elimination reactions between alkynes, including the strained cyclooctynes [14a] and linear alkynes, [14b] and N,N ‐dialkylhydroxylamines. The retro‐Cope elimination reaction, in analogy to a 1,3‐dipolar cycloaddition reaction, [7] proceeds with the formation of two new bonds between the H and N atoms of N,N ‐dialkylhydroxylamines with the triple bond of the alkyne, but is accompanied by the cleavage of the H−O bond to form a stable enamine N ‐oxide product (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…More recently, other bioorthogonal reactions have been developed, including strain‐promoted alkyne‐nitrone cycloadditions (SPANC), [11] isonitrile‐based [4+1] cycloadditions, [12] and cycloaddition reactions between o‐quinones and strained alkenes and alkynes [13] . Very recently, Kim and co‐authors introduced a new class of bioorthogonal reactions, i. e., the retro‐Cope elimination reactions between alkynes, including the strained cyclooctynes [14a] and linear alkynes, [14b] and N,N ‐dialkylhydroxylamines. The retro‐Cope elimination reaction, in analogy to a 1,3‐dipolar cycloaddition reaction, [7] proceeds with the formation of two new bonds between the H and N atoms of N,N ‐dialkylhydroxylamines with the triple bond of the alkyne, but is accompanied by the cleavage of the H−O bond to form a stable enamine N ‐oxide product (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Kim and co‐authors showed that the strategic modification at the terminal and propargylic positions of a linear alkyne can enhance its reactivity in the retro‐Cope elimination reaction with second‐order rate constants that rival similar strain‐promoted 1,3‐dipolar cycloaddition reactions (Scheme 2). [14a,b] The introduction of an electronegative halogen atom at the terminal position and positioning of an alkoxy group at the propargylic position of a linear alkyne can lead to a substantial acceleration of the retro‐Cope elimination reaction with N,N ‐diethylhydroxylamine and regioselective towards the anti ‐Markovnikov adduct ( anti‐ pathway) rather than the Markovnikov adduct ( syn ‐pathway) [14b] . Using DFT calculations, Kim and co‐authors found a correlation between the second‐order rate constants and the reduced s ‐character in the bonding orbital of the sp ‐hybridized carbon of the terminal‐modified alkynes [14b] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations